Ultrasonic characterization of the complex Young's modulus of polymer parts fabricated with microstereolithography. Issue 7 (8th October 2018) - Morris, Clinton B.; Cormack, John M.; Hamilton, Mark F.; Haberman, Michael R.; Seepersad, Carolyn C.
Abstract : Purpose: Microstereolithography is capable of producing millimeter-scale polymer parts having micron-scale features. Material properties of the cured polymers can vary depending on build parameters such as exposure. Current techniques for determining the material properties of these polymers are limited to static measurements via micro/nanoindentation, leaving the dynamic response undetermined. The purpose of this paper is to demonstrate a method to measure the dynamic response of additively manufactured parts to infer the dynamic modulus of the material in the ultrasonic range. Design/methodology/approach: Frequency-dependent material parameters, such as the complex Young's modulus, have been determined for other relaxing materials by measuring the wave speed and attenuation of an ultrasonic pulse traveling through the materials. This work uses laser Doppler velocimetry to measure propagating ultrasonic waves in a solid cylindrical waveguide produced using microstereolithography to determine the frequency-dependent material parameters of the polymer. Because the ultrasonic wavelength is comparable with the part size, a model that accounts for both geometric and viscoelastic dispersive effects is used to determine the material properties using experimental data. Findings: The dynamic modulus in the ultrasonic range of 0.4-1.3 MHz was determined for a microstereolithography part. Results were corroborated by using the same experimental method for an acrylic part with known properties and by evaluating the natural frequency and storage modulus of the same microstereolithography part with a shaker table experiment. Originality/value: The paper demonstrates a method for determining the dynamic modulus of additively manufactured parts, including relatively small parts fabricated with microstereolithography.